Hybrid origins of Australian honeybees (Apis mellifera) - (:unkn) unknown (My University, 2016)
Abstract With increased globalisation and homogenisation, the maintenance of genetic integrity in local populations of agriculturally important species is of increasing concern. The western honeybee (Apis mellifera) provides an interesting perspective as it is both managed and wild, with a large native range and much larger introduced range. We employed a newly created 95 single nucleotide polymorphism (SNP) test to characterise the genetic ancestry of the Australian commercial and feral honeybee populations. We found that most individuals were hybrids of mainly Western and Eastern European ancestry. Introductions of bees from North Africa are known from the historical record, and we show here the presence of alleles of African ancestry in some Australian bees, at levels comparable to those seen in the commercial populations of European-derived bees in North America.
Keywords: African Research